2004
DOI: 10.1039/b316804b
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear gold(i) complexes of bridging bidentate carbene ligands: synthesis, structure and spectroscopic characterisation

Abstract: Eight dinuclear Au(i)-carbene complexes have been synthesized from various imidazolium-linked cyclophanes and related acyclic bis(imidazolium) salts, by treatment of the imidazolium salts with [Au(i)(SMe(2))Cl] in the presence of a carboxylate base. Single crystal structural studies showed that the Au(i)-carbene compounds contain dinuclear (AuL)(2) cations in which a pair of gold(i) centres are linked by a pair of bridging dicarbenoid ligands. Interestingly, the structural studies revealed short AuAu contacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
163
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(178 citation statements)
references
References 27 publications
15
163
0
Order By: Relevance
“…[18b, 20] complex with two methylene-bridged, N-methylated bisimidazolylidene ligands were synthesized in order to properly compare their spectroscopic properties with those of 2 ( Figure 5). …”
Section: Scheme2synthesis Of Macrocyclic Tetranuclear Gold(i) Nhc Cmentioning
confidence: 99%
“…[18b, 20] complex with two methylene-bridged, N-methylated bisimidazolylidene ligands were synthesized in order to properly compare their spectroscopic properties with those of 2 ( Figure 5). …”
Section: Scheme2synthesis Of Macrocyclic Tetranuclear Gold(i) Nhc Cmentioning
confidence: 99%
“…Preliminary studies by Baker and co-workers 11 have shown that several dinuclear gold(I) complexes containing bridging NHC ligands induce membrane permeabilisation in rat liver mitochondria. This suggests that NHC-containing gold(I) complexes may be considered as promising alternatives to phosphine complexes in the development of chemotherapeutic agents.…”
mentioning
confidence: 99%
“…A number of dinuclear gold(I) carbene complexes with a 165 cyclophane-type carbene skeleton show good activity in the selective induction of mitochondrial permeability transition, 17 which is considered to be the primary mechanism leading to mitochondria-induced apoptosis. In addition, complex 12 comprising an ortho-substituted xylylene scaffold ( obtained as a mixture of syn and anti isomers (only syn isomer shown in Fig.…”
mentioning
confidence: 99%